Challenges in Evaluating Clinical Governance Systems in Iran: A Qualitative Study - Hooshmand, Elaheh (Kowsar, 2014)
BACKGROUND: In spite of the pivotal role of clinical governance in enhancing quality of services provided by hospitals across the country, a scientific framework with specific criteria for evaluating hospitals has not been developed so far. OBJECTIVES: This study was conducted with the aim to identify the challenges involved in evaluating systems of clinical governance in Iran. MATERIALS AND METHODS: For the purposes of this qualitative study, 15 semi-structured interviews with experts in the field were conducted in 2011 and the data were analyzed using framework analysis method. RESULTS: Five major challenges in evaluating clinical governance include managing human resources, improving clinical quality, managing development, organizing clinical governance, and providing patient-oriented healthcare system. CONCLUSIONS: Healthcare system in Iran requires a clinical governance program which has a patient-oriented approach in philosophy, operation, and effectiveness in order to meet the challenges ahead.